Unconventional magnetic order on the hyperhoneycomb Kitaev lattice in $β$-Li2IrO3: full solution via magnetic resonant x-ray diffraction - Biffin, A; Johnson, R; Choi, S; Freund, F; Manni, S; Bombardi, A; Manuel, P; Gegenwart, P; Coldea, R (American Physical Society, 2014)
The recently-synthesized iridate $β$-Li$_2$IrO$_3$ has been proposed as a candidate to display novel magnetic behavior stabilized by frustration effects from bond-dependent, anisotropic interactions (Kitaev model) on a three-dimensional "hyperhoneycomb" lattice. Here we report a combined study using neutron powder diffraction and magnetic resonant x-ray diffraction to solve the complete magnetic structure. We find a complex, incommensurate magnetic order with non-coplanar and counter-rotating Ir moments, which surprisingly shares many of its features with the related structural polytype "stripyhoneycomb" $γ$-Li$_2$IrO$_3$, where dominant Kitaev interactions have been invoked to explain the stability of the observed magnetic structure. The similarities of behavior between those two structural polytypes, which have different global lattice topologies but the same local connectivity, is strongly suggestive that the same magnetic interactions and the same underlying mechanism governs the stability of the magnetic order in both materials, indicating that both $β$- and $γ$-Li$_2$IrO$_3$ are strong candidates to realize dominant Kitaev interactions in a solid state material.